1996
DOI: 10.1128/iai.64.5.1614-1620.1996
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Chlamydia pneumoniae in vitro in human macrophages, endothelial cells, and aortic artery smooth muscle cells

Abstract: Chlamydia pneumoniae has recently been associated with atherosclerotic lesions in coronary arteries. To investigate the biological basis for the dissemination and proliferation of this organism in such lesions, the in vitro growth of C. pneumoniae was studied in two macrophage cell lines, peripheral blood monocyte-derived macrophages, human bronchoalveolar lavage macrophages, several endothelial cell lines, and aortic smooth muscle cells. Five strains of C. pneumoniae were capable of three passages in human U9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(130 citation statements)
references
References 34 publications
5
124
0
1
Order By: Relevance
“…Chlamydia pneumoniae has been associated with various chronic diseases such as asthma, coronary heart disease, and atherosclerosis (Campbell et al, 2000;Von Hertzen, 2002;Kuo & Campbell, 2003). Chlamydia pneumoniae is able to infect several cell types such as epithelial and endothelial cells, macrophages, monocytes and dendritic cells (DCs) (Gaydos et al, 1996;Airenne et al, 1999;Wittkop et al, 2006). Our previous studies revealed that C. pneumoniae colocalizes with DCs in temporal artery biopsies from patients with giant cell arteritis (GCA) (Wagner et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Chlamydia pneumoniae has been associated with various chronic diseases such as asthma, coronary heart disease, and atherosclerosis (Campbell et al, 2000;Von Hertzen, 2002;Kuo & Campbell, 2003). Chlamydia pneumoniae is able to infect several cell types such as epithelial and endothelial cells, macrophages, monocytes and dendritic cells (DCs) (Gaydos et al, 1996;Airenne et al, 1999;Wittkop et al, 2006). Our previous studies revealed that C. pneumoniae colocalizes with DCs in temporal artery biopsies from patients with giant cell arteritis (GCA) (Wagner et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The role of antibodies in terms of bacterium^host cell interactions has been studied in the in vitro L-929 infec-tion assays with S. minnesota Re and C. pneumoniae. Monocytes, macrophages, smooth muscle cells and endothelial cells have been shown to be susceptible for C. pneumoniae infection with regard to its link to coronary artery disease and atherosclerosis [12,13]. Fibroblasts may be a prominent cell type in chronic in£ammation and persistent infection.…”
Section: Resultsmentioning
confidence: 99%
“…vascular endothelial cells and smooth muscle cells, alveolar epithelial cells, fibroblasts, mononuclear cells, T-cells and dendritic cells, but also neuronal glia cells), which will almost invariably lead to enhanced expression of numerous inflammatory chemokines and cytokines [6,[30][31][32][33][34][35][36][37][38][39][40][41], which are usually regulated via small GTPase activation and subsequent activation of NF-jB heterodimers ( Table 1). Under in vitro conditions, vascular endothelial cells and smooth muscle cells are highly susceptible to C. pneumoniae infection [42,43], and develop a proatherosclerotic and proproliferative phenotype. This in vitro constellation might lead to complex vascular alterations in vivo, e.g.…”
Section: Inflammatory Response and Development Of An Atherogenetic Phmentioning
confidence: 99%